Thirty Years in the South Seas : Land and People, Customs and Traditions in the Bismarck Archipelago and on the German Solomon Islands. - Parkinson, Richard. (Sydney University Press, 2011)
In this 900-page work, Parkinson drew together and expanded on the scientific and popular papers he had been publishing since 1887, creating in the process a landmark ethnography of the Bismarck Archipelago.